2013
DOI: 10.1088/0957-4484/24/14/145301
|View full text |Cite
|
Sign up to set email alerts
|

Flexible organic solar cells including efficiency enhancing grating structures

Abstract: In this work, a new method for the fabrication of organic solar cells containing functional light-trapping nanostructures on flexible substrates is presented. Polyimide is spin-coated on silicon support substrates, enabling standard micro- and nanotechnology fabrication techniques, such as photolithography and electron-beam lithography, besides the steps required for the bulk-heterojunction organic solar cell fabrication. After the production steps, the solar cells on polyimide are peeled off the silicon suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…These approaches are based on plasmonic, diffraction and scattering effects, e.g., introduced by the integration of metallic nanoparticles near or in the photoactive layer, by the inclusion of metallic and non-metallic, aperiodic or (quasi-) periodic surface structures, or by the integration of randomly distributed metallic nanoparticles in the back contact layer 15–17 . There are several reports on nanostructured inorganic solar cell efficiency improvements as a result of enhanced optical absorption, which is a dominant factor to increase the overall performance and, in this case, directly translates to an increased photocurrent 18 .…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are based on plasmonic, diffraction and scattering effects, e.g., introduced by the integration of metallic nanoparticles near or in the photoactive layer, by the inclusion of metallic and non-metallic, aperiodic or (quasi-) periodic surface structures, or by the integration of randomly distributed metallic nanoparticles in the back contact layer 15–17 . There are several reports on nanostructured inorganic solar cell efficiency improvements as a result of enhanced optical absorption, which is a dominant factor to increase the overall performance and, in this case, directly translates to an increased photocurrent 18 .…”
Section: Introductionmentioning
confidence: 99%
“…By introducing a microstructured metal/dielectric interface to surmount the mismatch associated with the momentum of in-plane SPPs and incident photons, the SPP modes can be excited and the incident photons will be trapped and guided along the interface for a few micrometers until the energy is lost in metal and dielectric materials. The incident solar flux is transferred perpendicular to the incident direction and absorbed by the photoactive materials nearby the microstructured interface [105][106][107][108]. Forrest et al [108] have fabricated periodic 1-D metallic grating at the submicron scale based on nanolithography and explored their application in OPVs based on a small molecular active layer.…”
Section: Sppsmentioning
confidence: 99%
“…Following the Ti adhesion layer (3 nm), 80 nm layer of Al was deposited, followed by deposition of 20 nm layer of Ti. As TiOx has been used as an efficient electron transport layer in solar cells [14], we have oxidized the surface of the titanium layer by oxygen plasma [10]. For the samples containing gratings on the bottom-electrodes, electron beam lithography was employed for fabrication of titanium structures.…”
Section: Solar Cell Active Area Cpp Pedot:htl Solar Siliconmentioning
confidence: 99%
“…In order to fabricate the grating nanostructures on flexible substrates, we have used polyimide spin-coated on rigid Silicon substrates, allowing for the use of standard lithography techniques for electrode and grating definition. Our previous results have shown that gratings with pitch distances of 500 and 750 nm have a potential for enhancing the efficiency in flexible P3HT:PCBM solar cells [10]. In this work, we apply diffraction gratings in solar cells made of PCPDTBT:PCBM, a material combination that has a large potential for transparent solar cell applications [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation